(untitled) (International Journal of Physiology, 2019)
Measurement of carbon monoxide(CO) concentration in expired air canbe used for detecting and monitoring cytokine mediated inflammation and oxidative stress in the respiratory tract of smokers if smokers are made to abstain from smoking for 8 hrs. Total 48 apparently healthy male volunteers (24 were asymptomatic male tobacco smokers and rest 24 were healthy non-smoker males) with age between 18–25 years participated in the study. Exhaled CO level measured by the breath CO analyzer. Baseline Pulmonary function test(PFT) was done using RMS Helios Series Computer based Spirometer. Exercise challenge test was doneusing treadmill and PFT was recorded immediately, 5min., 10min. and 20min. of recovery period. Comparison of lung function before and after exercise in healthy volunteers and asymptomatic smokers respectively was done using paired t test. Correlation between post exercise percentage change in FEV1 and exhaled COwas seen using Pearson’s coefficient of correlation. A negative correlation was found between CO concentration in exhaled breath and improvement in FEV1 after exercise challenge test. Hence, Breath CO analyser can be used to measure endogenous CO in so called “healthy smokers” as a tool to detect early inflammation and also to motivate them to quit smoking before the disease becomes irreversible.